Comparative Analysis of Legal Protection and Psychological Impact on Child Victims of Sexual Violence: A Study of Jurisdiction A and Jurisdiction B - Anton Adreas Sihotang; Sarma Situmorang; Dediono Dediono; Manahara Siahaan (Jurnal Sosial, Sains, Terapan dan Riset (Sosateris), 2021)
Child victims of sexual violence face significant legal and psychological challenges that can vary based on the jurisdiction they reside in. This research presents a comparative analysis of the legal protection and psychological impact experienced by child victims of sexual violence in two jurisdictions, Jurisdiction A and Jurisdiction B. The study employs a mixed-methods approach, combining legal framework analysis and psychological impact assessment to examine the interplay between legal safeguards and psychological well-being. The legal framework analysis reveals that Jurisdiction B offers more comprehensive legal protection for child victims, characterized by higher age of consent and well-structured reporting mechanisms. In contrast, Jurisdiction A has a lower age of consent and less robust reporting mechanisms, potentially leaving certain cases inadequately addressed. Psychological impact assessments of child victims in both jurisdictions indicate that Jurisdiction B's stronger legal protection correlates with lower levels of psychological distress. Child victims in Jurisdiction A tend to experience higher levels of anxiety and fear due to insufficient legal protection. Conversely, those in Jurisdiction B report a greater sense of security and empowerment, leading to less severe psychological impact. The findings underscore the positive correlation between effective legal protection and positive psychological outcomes for child victims of sexual violence. Moreover, a holistic approach involving collaboration between legal and psychological sectors is crucial to support the healing and recovery of child victims. However, this study acknowledges its limitations in generalizing results across different contexts and cultures